Remote ischemic preconditioning in cyanosed neonates undergoing cardiopulmonary bypass: A randomized controlled trial - Jones, B; Pepe, S; Sheeran, F; Donath, S; Hardy, P; Shekerdemian, L; Penny, D; McKenzie, I; Horton, S; Brizard, C; D'Udekem, Y; Konstantinov, I; et al. (2013)
Objective: The myocardial protective effect of remote ischemic preconditioning has been demonstrated in heterogeneous groups of patients undergoing cardiac surgery. No studies have examined this technique in neonates. The present study was performed to examine the remote ischemic preconditioning efficacy in this high-risk patient group. Methods: A preliminary, randomized, controlled trial was conducted to investigate whether remote ischemic preconditioning in cyanosed neonates undergoing cardiac surgery confers protection against cardiopulmonary bypass. Two groups of neonates undergoing cardiac surgery were recruited for the present study: patients with transposition of the great arteries undergoing the arterial switch procedure and patients with hypoplastic left heart syndrome undergoing the Norwood procedure. The subjects were randomized to the remote ischemic preconditioning or sham control groups. Remote ischemic preconditioning was induced by four 5-minute cycles of lower limb ischemia and reperfusion using a blood pressure cuff. Troponin I and the biomarkers for renal and cerebral injury were measured pre- and postoperatively. Results: A total of 39 neonates were recruited - 20 with transposition of the great arteries and 19 with hypoplastic left heart syndrome. Of the 39 neonates, 20 were randomized to remote ischemic preconditioning and 19 to the sham control group. The baseline demographics appeared similar between the randomized groups. The cardiopulmonary bypass and crossclamp times were not significantly different between the 2 groups. The troponin I levels were not significantly different at 6 hours after cardiopulmonary bypass nor were the postoperative inotrope requirements. Markers of renal (neutrophil gelatinase-associated lipocalin) and cerebral injury (S100b, neuron-specific enolase) were not significantly different between the 2 groups. Conclusions: Our data suggest that remote ischemic preconditioning in hypoxic neonates undergoing cardiopulmonary bypass surgery does not provide myocardial, renal, or neuronal protection. Additional studies are needed to examine the relationships among developmental age, hypoxia, and the molecular mechanisms of ischemic preconditioning. Copyright © 2013 by The American Association for Thoracic Surgery.